1999
DOI: 10.1088/0954-3899/25/8/314
|View full text |Cite
|
Sign up to set email alerts
|

Backward-forward analysis of fast and slow hadrons in6Li interactions with emulsion nuclei at 3.7 A GeV

Abstract: A comparison of the recent experimental results on yields of s, g and b-particles (fast and slow hadrons) emitted in the forward (θ < 90 • ) and backward (θ 90 • ) hemispheres resulting from the interactions of 6 Li (3.7 A GeV) with emulsion nuclei is made with two theoretical models: a typical intranuclear cascade model and a modified FRITIOF model. The latter consists of two main ingredients: (i) the distribution of the nucleons knocked out by hard collisions based on a classical Glauber approach and (ii) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The pion source varies according to the energy, system size, centrality, and emission zone. Our lab group has concerned it [10,[16][17][18][19][20][24][25][26][27][28][29][30][31][32][33]. The present interactions are 3.7 A GeV 4 He, 16 O, and 32 S with emulsion nuclei.…”
Section: Introductionmentioning
confidence: 84%
“…The pion source varies according to the energy, system size, centrality, and emission zone. Our lab group has concerned it [10,[16][17][18][19][20][24][25][26][27][28][29][30][31][32][33]. The present interactions are 3.7 A GeV 4 He, 16 O, and 32 S with emulsion nuclei.…”
Section: Introductionmentioning
confidence: 84%
“…The backward emission of protons and pions in hadron-nucleus [1][2][3][4][5][6][7] and nucleus-nucleus [8][9][10][11][12][13][14][15][16][17][18] at relativistic energies have been investigated exclusively. It is found that the backward proton production was attributed to the absorption of secondary pions by a nucleon pair in the target nucleus, and the backward pions production shown to be consistent with the cumulative effect [19].…”
Section: Introductionmentioning
confidence: 99%
“…The study of the production of backward particles in hadron-nucleus and nucleus-nucleus interactions at high energies has received considerable experimental and theoretical attention because the fact that the backward emission of relativistic particles in high energy hadronnucleon collisions is kinematically restricted. The backward emission of protons and pions in hadron-nucleus [1][2][3][4][5][6][7] and nucleus-nucleus [8][9][10][11][12][13][14][15][16][17][18] at relativistic energies have been investigated exclusively. It is found that the backward proton production was attributed to the absorption of secondary pions by a nucleon pair in the target nucleus, and the backward pions production shown to be consistent with the cumulative effect [19].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we analyze the data on shower and grey particles produced in the backward (90 • θ 180 • , where θ is the emission angle in the laboratory system) hemisphere and forward (0 • θ 90 • ) hemisphere from the interaction of 16 O projectile with emulsion nuclei at 4.5 AGeV/c. This research focused on the general characteristics of multiplicity distributions of backward shower and grey particles and compared them systematically with the corresponding ones obtained for other projectiles at nearly the same incident momentum per nucleon [16][17][18][19][20][21][22][23][24][25] . Furthermore, the multiplicity correlations between dif-…”
Section: Introductionmentioning
confidence: 99%